Food allergy knowledge, attitudes, and resources of restaurant employees. Issue 11 (5th November 2018) - McAdams, Bruce; Deng, Allison; MacLaurin, Tanya
Abstract : Purpose: Restaurants are unique and challenging environments for accommodating food allergies. The purpose of this paper is to evaluate food allergy knowledge, attitudes and resources among restaurant employees, and identify differences based on restaurant mode of operation. Design/methodology/approach: A total of 209 food-service workers were surveyed in full-service restaurants across Southern Ontario, Canada. A paper-based questionnaire was used to evaluate participants' food allergy knowledge, attitudes toward handling food allergy requests and emergencies, and the availability of food allergen resources at the restaurant. Findings: Most participants were knowledgeable about food allergies, and valued being able to provide safe meals. However, there was a general lack of access to important food allergy risk management resources and training. Food allergy attitudes were significantly different between restaurant modes of operation. Also, food allergy training and resources were positively correlated with employee attitudes toward food allergies. Practical implications: The results of this study show that engaging employees in food allergy training can contribute to greater levels in employee awareness and confidence in protecting health and safety of restaurant patrons with food allergies. Restaurants that demonstrate a strong preparedness toward handling food allergy requests can deliver a better customer experience and increase customer loyalty. Originality/value: The findings of this study underscore the need for the restaurant industry, policy makers and food safety educators to work together to develop training programs and relevant resources to support and facilitate food allergy risk management in restaurants.